Disaster nursing competencies of rural nurses during COVID-19: A cross-sectional study. Issue 2 (April 2023) - Jang, Sun Joo; Cho, Sunhee
Abstract : Background: Although rural nurses' roles are indispensable in coronavirus disease 2019 (COVID-19) management, increased roles, workload, burnout, and reduced job satisfaction can hinder their work, potentially affecting nurses' disaster nursing competencies. Aim: The aim of the study was to identify the predictors of rural nurses' disaster nursing competencies during the COVID-19 pandemic. Methods: Nurses from rural community hospitals in South Korea (N=204) were surveyed during June–July 2021. We used the Professional Quality of Life and Disaster Nursing Preparedness-Response Competencies questionnaires. Multiple regression analysis was performed to identify the predictors of disaster nursing competencies. Findings: The mean score for disaster nursing competency of the 204 participants was 110.80 (standard deviation=19.14). Disaster nursing competencies correlated with age, nursing career, compassion satisfaction, and secondary traumatic stress. Compassion satisfaction (β=.27, P =.004), prior disaster nursing education (β=.19, P =.005), and prior participation in disaster nursing care (β=.16, P =.022) predicted disaster nursing competencies, together accounting for 24.2% of the variance. Discussion: Our findings imply that increasing opportunities for continuing education regarding disaster nursing is crucial to enhance the related competencies in rural nurses. This study also highlights the necessity for stakeholders to develop programs aimed at increasing rural nurses' compassion satisfaction. Conclusion: Prior disaster nursing education, prior participation in disaster nursing care, and compassion satisfaction predicted disaster nursing competencies among rural nurses, with compassion satisfaction being the strongest predictor.